2020
DOI: 10.1039/c9ew01023h
|View full text |Cite
|
Sign up to set email alerts
|

Field testing of low-cost titania-based photocatalysts for enhanced solar disinfection (SODIS) in rural India

Abstract: We report the efficacy of titania-based photocatalysts for use as a simple and effective method of disinfecting drinking water in villages in West Bengal, demonstrating the viability of this technique to enhance solar disinfection in rural areas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However, the exact role and the mechanism of microbial disinfection was discovered during the 20th century when Aftim Acra et al conducted and published a similar work explaining how sunlight disinfects water microorganisms [33,34]. Since then, a significant number of studies have been conducted revealing the great potential of SODIS in inactivating pathogenic microorganisms in water [35,36].…”
Section: Solar Disinfection and Water Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the exact role and the mechanism of microbial disinfection was discovered during the 20th century when Aftim Acra et al conducted and published a similar work explaining how sunlight disinfects water microorganisms [33,34]. Since then, a significant number of studies have been conducted revealing the great potential of SODIS in inactivating pathogenic microorganisms in water [35,36].…”
Section: Solar Disinfection and Water Treatmentmentioning
confidence: 99%
“…In the photocatalytic disinfection process using normal sunlight, it was found that using photocatalysts (semiconductors) with suitable optical band-gap for the generation of reactive oxygen species in the presence of solar-light can significantly enhance the inactivation of microorganisms [35,129]. Several solar light/visible light metallic and even non-metallic photocatalysts have been investigated and proven to have a significant photocatalytic potential at laboratory scale [130,131].…”
Section: Continuous Flow Sodis Systemmentioning
confidence: 99%
“…Reactors with compound parabolic collectors concentrate solar irradiation to increase water disinfection efficiency, yet high initial investments can be cost-prohibitive for rural LMIC households . Other methods apply additives such as hydrogen peroxide, sodium percarbonate, Fenton reagents, semiconductor photocatalysts, and organic photosensitizers. , These modifications increase the concentration of reactive species and accelerate disinfection kinetics at relatively low costs. Even so, it has been challenging to provide a rural household practicing SODIS with regular access to these additives .…”
Section: Introductionmentioning
confidence: 99%
“…Semiconductor photocatalysis has attracted much attention in recent years as a potential method to address global drinking water demands, [1][2][3] including initial demonstration in rural Indian villages. 3 Photogenerated production of reactive holes, electrons and reactive oxygen species has been proven to be an effective strategy to destroy many contaminants commonly present in water sources. 4 Thus far, much of the reported work focuses upon titanium dioxide (TiO 2 ).…”
Section: Introductionmentioning
confidence: 99%